Functional barriers and their incidencce in the exportable supply of the Micro and Small Enterprise (MSE) in the textile and clothing sector - Macha Huamán, Roberto (2018)
Objective: To determine how the functional barriers faced by MSE in the textile and clothing sector influence the exportable supply. The functional barriers that were identified are: Human Resources, Production and Finance. Method: The present investigation is defined under the quantitative approach, descriptive and correlational type and non-experimental design. Results: The population and sample is not probabilistic or directed, it is conformed by fourteen (MSE) from the textile sector, which have exported between the years 2006-2016 and have been in the process of internationalization on a regular basis for a period of not less than five years. Conclusions: The deficiencies in the areas of human resources, production and finances, generate limitations in 50% of the export (MSE) becoming functional barriers that affect the exportable supply while the remaining 50%, has few limitations overcoming functional barriers and obtaining better results in its exportable offer. In this sense, according to Spearman's Rho correlation coefficient, which analyzes the correlation and the level of significance between the two variables, it is established that the functional barriers faced by the(MSE) exporters of the textile and clothing sector have a negative influence on the exportable supply.